Severe gastrointestinal involvement in pediatric IgA vasculitis: a retrospective single-center cohort study in China - Li, Yifan; Zhang, Xiaomei; Liu, Haimei; Li, Guomin; Guan, Wanzhen; Zhang, Tao; Zeng, Qiaoqian; Gong, Yinv; Xu, Hong; Sun, Li (Frontiers in Pediatrics, 2023)
Objectives: To describe the characteristics of gastrointestinal (GI) involvement in a cohort of hospitalized children with IgAV in China. Method: We reviewed the records of hospitalized IgAV patients from January 2014 to December 2020 at one tertiary medical center. According to whether there was massive GI bleeding and complications, patients were divided into severe and non-severe GI groups. The clinical manifestations, laboratory factors and treatment were analyzed between the two groups. Results: There were 1179 patients hospitalized for IgAV. GI involvement was noted in 50% (589) of the patients, of whom 288 (48.9%) patients had severe GI involvement. GI complications were observed in 34 patients with GI involvement IgAV. Rare onset age (<3, or 13-17), purpura above the waist, vomiting, high neutrophil to lymphocyte ratio and decreased serum albumin were factors associated with severe GI involvement. Frequencies of renal involvement and biopsy-proven nephritis were higher in the severe GI group. The most commonly used medications were corticosteroids (100.0%) in the severe GI group. The maximum corticosteroid dose was higher (2.9 vs. 2.0 mg/kg), and more second-line therapies were needed (30.9% vs. 16.94%) in the severe GI group. Conclusions: Severe GI involvement in children is common in our center. Rare onset age, purpura above the waist, vomiting, high neutrophil to lymphocyte ratio and decreased serum albumin are associated with severe GI involvement. Patients with severe GI involvement need higher doses of corticosteroids and second-line therapy.